2012
DOI: 10.5539/esr.v2n1p165
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biogas Production Yields of Different Waste Materials

Abstract: Biogas production from three different sources namely, cattle manure, cheese whey and blood, which have different characteristics, were investigated comparatively. Biogas production rates of 0.63, 0,72 and 0,64 l min PO were observed in 30 days of digestion of manure. The amount of total nitrogen (Tot-N) decreased 10% in 30 days of digestion but ammonium-nitrogen (Am-N) increased 46% at the same duration of time. Manure, during co-digestion, buffered and inoculated the cheese whey and blood, and converted them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…The least performed digester is digester E with 100% MH. This abysmal performance obtained in digester B could be linked to the high C/N ratio (Table 1), above the recommended limit of 20-35 [9,23] and higher lignin content [16]. While high C/N ratio results in acidification which inhibits methanogenic activities ( [23]), high lignin content inhibits initial hydrolysis of substrates.…”
Section: Resultsmentioning
confidence: 97%
“…The least performed digester is digester E with 100% MH. This abysmal performance obtained in digester B could be linked to the high C/N ratio (Table 1), above the recommended limit of 20-35 [9,23] and higher lignin content [16]. While high C/N ratio results in acidification which inhibits methanogenic activities ( [23]), high lignin content inhibits initial hydrolysis of substrates.…”
Section: Resultsmentioning
confidence: 97%
“…Digester B was found to have higher biogas yield than the other digesters, followed by digester C. The least performed digester is digester E with 100% MH. This could have resulted from the very high C/N ratio, above the recommended limit of 20-35 (Ghasimi et al, 2009;Ozturk, 2013), and higher lignin content (Momoh and Nwaogazie, 2011). While very high C/N ratio results in acidification which inhibits methanogenic activities (Ozturk, 2013), high lignin content inhibits initial hydrolysis of substrates (Momoh and Nwaogazie, 2011) After the 44 days of digestion, total biogas produced for digesters A, B, C, D and E was found to be 11.10, 15.64, 11.84, 6.65, and 5.24 L/gVS respectively (Fig.…”
Section: Biogas Production At Different Fw and Mh Mixturesmentioning
confidence: 99%
“…Ozturk [91] investigated AD of blood as a mono-substrate in semi-continuous 3.6 m 3 working volume continuously mixed digester operated at 35 • C with an HRT of 18 days. No methane was observed, but a strong offensive odor was produced; therefore, it was concluded that AD of blood alone is difficult, and feeding another organic waste as a co-digestate is suggested.…”
Section: Previous Studies On Blood Anaerobic Digestionmentioning
confidence: 99%
“…Integrating the concepts of co-digestion and dilution, Ozturk [91] co-digested cattle blood:cattle manure:water (30:20:50 mass ratio) in a semi-continuous 3.6 m 3 working volume continuously mixed digester operated at 35 • C with an HRT of 18 days. They reported a biogas production rate of 0.64 L min −1 m −3 with a COD removal of 34% in a 30-day study.…”
Section: Previous Studies On Blood Anaerobic Digestionmentioning
confidence: 99%
See 1 more Smart Citation